Influence of Gibberellic acid (GA3) on seed germination and seedling growth of Kagzi Lime - D. Moharana, W. S. Dilip, D. Singh; Rout, Sandeep; Patra, S. (Journal of Scientific Agriculture, 2018)
A study was conducted to estimate the influence of gibberellic acid (GA3) at different concentrations in different time intervals on seed germination and seedling growth of kagzi lime. The results revealed that Maximum germination percentage (95%) was recorded under treatment with GA3 80 ppm for 12 hours, rate of germination of seeds (25 days), height of plant (18.79 cm) at 120 DAS, number of leaves per plant (26.53), fresh and dry weight of shoot (25.84 g and 14.44 g), tap root (17.44 cm), secondary and fibrous roots (5.98 and 85.99), fresh as well as dry weight (7.04 and 4.95 g), survival percentage (85 percent) in similar treatment. Therefore, it may be concluded that the GA3 at 80 ppm has a significant effect on the seed germination and seedling growth of Kagzi Lime and can be recommended to the grower for obtaining better growth and yield.